Cafein and Infertility on Women - Fedriani, Jessica; Surja, Sem Samuel (The Journal of The Indonesian Medical Students Association, 2010)
Caffeine is a natural compund in many food and, such as coffee, tea, cocoa, and others. Indonesia is classified as one of the country which consume high number of caffeine. Eventhough caffeine can stimulate central nervous system, it may also bring undesireable effect such as infertility. Through this paper, we would like to review the effect of caffeine on females fertility and the safety limit of caffeine for daily consumption on women. This paper is made with study literature method. There are several studies which indicate that there is a strong relationship between caffeine consumption and infertility. The safety limit of the amount of caffeine that may affect fertility requires more research. Daily consumption of a cup of non-decaffeinated coffee of more showed a significant impact on fertility. There is greater risk of infertility at women who consume the greater amount of caffeine.ÃÂ Key words: caffeine, infertility